2015
DOI: 10.1111/mmi.13202
|View full text |Cite
|
Sign up to set email alerts
|

Osmoporin OmpC forms a complex with MlaA to maintain outer membrane lipid asymmetry in Escherichia coli

Abstract: SummaryGram-negative bacteria can survive in harsh environments in part because the asymmetric outer membrane (OM) hinders the entry of toxic compounds. Lipid asymmetry is established by having phospholipids (PLs) confined to the inner leaflet of the membrane and lipopolysaccharides (LPS) to the outer leaflet. Perturbation of OM lipid asymmetry, characterized by PL accumulation in the outer leaflet, disrupts proper LPS packing and increases membrane permeability. The multi-component Mla system prevents PL accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
195
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(200 citation statements)
references
References 52 publications
(89 reference statements)
5
195
0
Order By: Relevance
“…However, due to its toxicity, the yebT-expressing plasmid did not complement the hypersensitivity (data not shown). It was reported that the Mla pathway depends on OmpC porin for its function (21). However, even in the ΔmlaD ompC background, deletion of both the pqiABC and yebST operons rendered cells sensitive to SDS-EDTA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to its toxicity, the yebT-expressing plasmid did not complement the hypersensitivity (data not shown). It was reported that the Mla pathway depends on OmpC porin for its function (21). However, even in the ΔmlaD ompC background, deletion of both the pqiABC and yebST operons rendered cells sensitive to SDS-EDTA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some ABC transports are involved in the biogenesis of the outer membrane and are important for maintaining outer membrane integrity and stability (50,54,55). Disruption of such transporters adversely affects membrane integrity and stability, which in turn affects the cell's susceptibilities to toxic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in contrast to PldA, which requires calcium for activity, PagP levels are increased by the PhoPQ stress response under conditions of divalent cation limitation [55,58]. In addition to fortifying the OM barrier, palmitoylated lipid A can also alter the innate immune response and has proven a useful experimental tool as a probe to monitor ectopic exposure of PLs in the OM [50,59,60]. Although the fate of the lyso-PL by-products of PagP activity is unclear, systems exist to recycle these lipids [61,62], which will be discussed further in Section 4.1…”
Section: – Maintenance Of Om Asymmetrymentioning
confidence: 99%
“…How phospholipids could be flipped to the inner leaflet of the OM, which is devoid of an obvious energy source, is not yet clear. The OM lipoprotein component MlaA has been shown to interact with the OM protein porin OmpC, and deletion of this porin has a similar phenotype to mlaA null mutants under some, but not all, conditions [59]. These observations led to the proposal that the porin may facilitate transbilayer movement of mislocalized PLs [59].…”
Section: – Maintenance Of Om Asymmetrymentioning
confidence: 99%